MRCP Helps in Chronic Pancreatitis Complicated with Obstructive Jaundice - Sindhu, R. S. (Indian J Surg, 2014)
When chronic pancreatitis (CP) presents with obstructive jaundice, though there is a risk for malignancy, possibility of benign biliary stricture should also be considered on treatment planning. Imaging and tumour markers have limitations in distinguishing benign and malignant lesions in CP. Here, MRI has effectively picked up a mass lesion as the cause for obstructive jaundice in CP; the patient underwent pancreaticoduodenectomy and the histopathology proved it as adenocarcinoma in CP.